Bacterial Infection and Hematological Parameters of aborted women in Thi-Qar province, Iraq - Wdaa , Qasim Hassan (University of Thi-Qar Journal of Science, 2019)
The Current study was performed among 40 aborted women whom referred Bint-AL Huda teaching hospital in Thi-Qar province, Iraq. During the period from August 2012 to April 2013. Vaginal swabs were collected, cultured and their susceptibility to various antibiotics was determined, A significant growth was obtained in (23) samples, Staphylococcus aureus, Escherichia coli was the most prevalent isolates. Blood sample were collected to perform complete blood count. Hematologic tests through complete blood count showed that the values of White blood cell count, Neutrophil, Lymphocyte, Monocyte and Eosinophil count was a significant higher in abortive women compare to the control group. But the study revealed significant decrease in hemoglobin level and red blood cell count of aborted women compared to control group